Exploring the Landscape of Research on Enterprise Green Environments Through Science Mapping Analysis - Feng Hu (Tehnički Vjesnik, 2024)
This study employs science mapping and bibliometric analysis to chart the knowledge structure and research trajectory of enterprise green environment literature from 2002 to 2022. Despite rising interest, comprehensive analyses of this field's research landscapes and dynamics remain scarce. Through advanced techniques including discipline mapping, journal co-citation analysis, author co-citation analysis, and keyword co-occurrence analysis, this work elucidates the prominent disciplines, publications, authors, and research foci in enterprise of green environment scholarship over the past two decades. The results provide vital insights into the current status, influential leaders, core journals, knowledge gaps, and future directions of this rapidly evolving field. This science mapping analysis offers a valuable quantitative overview of green environment research enterprise that can inform scholars worldwide in producing impactful work on this critical area. The findings reveal profound implications for the developing structure and frontiers of sustainability-focused business and management research.